PERAN KINERJA GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Fatma Dewi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The principal problem this reseach is how to the role of teachers in improving performance achievments learn students of class IV elementary school of 8 Pulau Rimau. This study using the thedescriptive, where the reseach used to describe the exact phenomenon hapenned in elementary school of 8 Pulau Rimau, Collecting the methods used data is observasi, inquiries, and the seach reference. Then the tecniques processing data and data analysis done to use a technique a quantitative analysis thedescriptive.The result of reseach shows that the role of performance of the teacher good enough in improving the achievments learn students of class IV in elementary school of 8 Pulau Rimau, it can be determined by the behavior of the existence of a good is evidence that the teacher can attract the attention of students. And about of the accomplishments of learning students in elementary shcool of 8 Pulau Rimau can be seem from the undestanding of the lessons that can be used a as reject the succes of students in lerning.